2015
DOI: 10.14814/phy2.12432
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of V̇O2slow component by priming exercise: novel mechanistic insights from time-resolved near-infrared spectroscopy

Abstract: Novel time-resolved near-infrared spectroscopy (TR-NIRS), with adipose tissue thickness correction, was used to test the hypotheses that heavy priming exercise reduces the V̇O2 slow component (V̇O2SC) (1) by elevating microvascular [Hb] volume at multiple sites within the quadriceps femoris (2) rather than reducing the heterogeneity of muscle deoxygenation kinetics. Twelve subjects completed two 6-min bouts of heavy work rate exercise, separated by 6 min of unloaded cycling. Priming exercise induced faster ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 62 publications
(164 reference statements)
3
27
0
Order By: Relevance
“…An additional novel feature of this study was the application of TRS-NIRS within an increased number of active muscle sites (other than the VL) following PLA and BR supplementation. In line with previous studies (Koga et al 2007(Koga et al , 2011Chin et al 2011;Fukuoka et al 2015), this revealed inter-muscular differences in deoxy [Hb + Mb] profiles which may be explained by disparities in muscle fiber type (Johnson et al 1973;Lexell et al 1983) and/or activity level (Chin et al 2011) between skeletal muscles. However, there were no significant differences in the inter-site CV of the deoxy [Hb + Mb] MRT p or A p between PLA and BR supplementation.…”
Section: Effect Of Br Supplementation On the Spatial Heterogeneity Ofsupporting
confidence: 91%
See 3 more Smart Citations
“…An additional novel feature of this study was the application of TRS-NIRS within an increased number of active muscle sites (other than the VL) following PLA and BR supplementation. In line with previous studies (Koga et al 2007(Koga et al , 2011Chin et al 2011;Fukuoka et al 2015), this revealed inter-muscular differences in deoxy [Hb + Mb] profiles which may be explained by disparities in muscle fiber type (Johnson et al 1973;Lexell et al 1983) and/or activity level (Chin et al 2011) between skeletal muscles. However, there were no significant differences in the inter-site CV of the deoxy [Hb + Mb] MRT p or A p between PLA and BR supplementation.…”
Section: Effect Of Br Supplementation On the Spatial Heterogeneity Ofsupporting
confidence: 91%
“…; Fukuoka et al. ), this revealed inter‐muscular differences in deoxy [Hb + Mb] profiles which may be explained by disparities in muscle fiber type (Johnson et al. ; Lexell et al.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hence, in addition to an improved P O 2 mv , an alternative mechanism by which priming exercise might have resulted in the independent improvement of τV O 2 and critical power in the supine position is via a reduced heterogeneity of muscle deoxygenation. Such a hypothesis remains to be tested; however, previous research has indicated no relationship between the change in muscle deoxygenation heterogeneity and the slow component of pulmonaryV O 2 kinetics with priming exercise (Saitoh et al 2009;Fukuoka et al 2015).…”
Section: The τV O2 -Critical Power Relationship During Upright and Sumentioning
confidence: 96%